2014
DOI: 10.1016/j.gexplo.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Lead accumulation in plants grown in polluted soils. Screening of native species for phytoremediation

Abstract: In the present work, we focused on soils contaminated with elevated lead concentrations in an agricultural and residential area surrounding a lead smelter plant in Bouwer, province of Córdoba, Argentina. The aim of this research work was to assess the phytoextraction suitability of native plant species growing in the vicinity of a former lead smelter.The lead concentration in leaves, stems and roots was determined in ten species collected at ten sampling sites along a lead concentration gradient in soil. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 30 publications
2
47
0
2
Order By: Relevance
“…The increased leaf thickness reduces CO 2 assimilation, transpiration and stomatal conductance in the plants planted on roadside. The relationship between traits of present study is similar to other studies conducted worldwide (Stanghellini and van Meurs 1992;Emberson et al 2001;Salazar and Pignata 2014;Khedhar and Gadge 2014;Jochner et al 2015;Calfapietra et al 2015).…”
Section: Response Of Biochemical Indicators: Lead and Proline In Leafsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased leaf thickness reduces CO 2 assimilation, transpiration and stomatal conductance in the plants planted on roadside. The relationship between traits of present study is similar to other studies conducted worldwide (Stanghellini and van Meurs 1992;Emberson et al 2001;Salazar and Pignata 2014;Khedhar and Gadge 2014;Jochner et al 2015;Calfapietra et al 2015).…”
Section: Response Of Biochemical Indicators: Lead and Proline In Leafsupporting
confidence: 91%
“…Wagela et al (2002) reported maximum accumulation of lead content in leaf tissue of Dalbergia sissoo grown at roadside in urban area of Indore city of India and findings was similar to this study. Lead accumulation in leaves of trees was also reported by Salazar and Pignata (2014) under polluted environment. The study carried out at worldwide and under this study showed that lead and proline accumulation in leaf tissues in plants of urban area can be used as indicator of tolerance and adaption for screening of plant species which can uptake and absorb the higher amount of heavy metals and could be planted under urban area where air pollution is supposed to be more in future due to traffic movements and other anthropogenic pressure.…”
Section: Response Of Biochemical Indicators: Lead and Proline In Leafmentioning
confidence: 61%
“…In their study Lalor et al (1998) reported a wide range of Cd concentrations in non-mineralized Jamaican soils. Similarly, Salazar and Pignata (2014) reported high level of lead exceeding national and international norms in soils and native plants in Córdoba, Argentina. Uptake and transfer of heavy metals through food crops are affected by the level of metals in soils, soil properties, pH, age of food crop, food crop types and species (Rafiq et al 2014;Xu et al 2015;Yang et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…As the uptake of Pb from the soil increases, it can damage the ultrastructures of the organs, tissues, chloroplast, mitochondria, nucleus, cell wall, and cell membrane in the plants. This damage can cause a loss of organelle function, and can eventually affect the normal physiological functions that include photosynthesis, respiration, protein synthesis, cell division within the plant species (Salazar and Pignata, 2014 (Pourrut et al, 2011). Yang and Ye (2014 ) reported significant differences among plants in their Pb tolerance and uptake in the shoots and the roots.…”
Section: Introductionmentioning
confidence: 99%